Upanyas Samrat Munshi Premchand: A Social Reformer - Surendra Kumar , Gupta (International Journal of Psychosocial Rehabilitation, 2016)
The advent of Modern period in Hindi is considered from the 1900’s. In the beginning modern Hindi literature was centered on the magical and fairy tales, entertaining the readers with imagination. Born as Dhanpat Rai Srivastav, he began his career as a freelance writer under the pen name “Nawab Rai”, but when his work ‘soz-e- watan’, a collection of short stories was seized by the British government and burnt, after this he started writing in Hindi, with the name Mushi Premchand. Premchand usually referred to as the ‘Tolstoy of India’ shaped the Hindi literature into a reality. He conquered the literary genre as a novelist, story writer and as a dramatist, and istitled as the ‘Upanyas Samrat’ (Emperor of Novels) in Hindi Modern literature. He gave a new dimension to the Hindi literary world by depicting reality of the society to the readers. He entered the Hindi literary world in the year 1917 with his novel, ‘Sevasadan’. He has penned 17 novels and more than 300 short stories whichportrayed the social issues prevalent in the society during his time. He raised his voice against the feudal system, the zamindari system, poverty, communalism, caste system, and the social and economic conditions prevalent in the society. He even mentioned the discrimination the females faced in the society. He fought against the dowry system, widow marriages and opined that women have to come out and express her feelings against the social evils and discriminations showed on her. He wrote on the life around him and made the readers aware about the social structure around them. He portrayed the common man in his work’s giving them the status of heroes and heroines by depicting the problems faced by them. Thus he presents to us the real India. The review highlight’s how Premchands works have influenced various genres of Hindi literature about the social issues and the struggle of the poor and how through the characters the change that could be brought in.Premchand’s works also portrayed the women in society who can be classified into traditional, modern women. The following literature review attempts to demonstrate and support the objective of the study.